Modern Organization Theory and Critical Organization Theory - Akdila Bulanov; Afri Wandi Zahri Ramadhan; Nabila Sukma; Putri Varisya (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article discusses the development of organizational theory, from modern organizational theory to basic organizational theory, and its application. The research background is driven by the evolution of organizations from the post-Industrial Revolution to the digital era, where modernism emphasized efficiency and environmental adaptation, while critical approaches exposed power, capitalist ideology, and worker alienation. The research objective is to analyze the development of organizational theory from the modern to the critical paradigm and its application to contemporary organizational management in Indonesia. The method used is a literature review with a qualitative approach to collect and analyze relevant sources. The research results found that the integration of both theories produces a